2023
DOI: 10.1096/fj.202201856r
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of MGF‐110‐9L gene from African swine fever virus weakens autophagic degradation of TBK1 as a mechanism for enhancing type I interferon production

Abstract: African swine fever (ASF) caused by African swine fever virus (ASFV) is a devastating disease for the global pig industry and economic benefit. The limited knowledge on the pathogenesis and infection mechanisms of ASF restricts progress toward vaccine development and ASF control. Previously, we illustrated that deletion of the MGF-110-9L gene from highly virulent ASFV CN/GS/2018 strains (ASFV∆9L) results in attenuated virulence in swine, but the underlying mechanism remains unclear. In this study, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In general, this study identified a potential target for the development of novel antiviral therapeutic strategies. On the other hand, based on current research findings, many viral proteins participated in the regulation of autophagy, such as A137R, MGF-505-7R, K205R, L83L, E199L, A179L, and MGF-110-9L ( 38 , 40 43 , 53 , 54 ). Thus, we concluded that autophagy may play an important role in the regulation of ASFV replication, and the mechanism between viral protein and autophagy deserves further study.…”
Section: Discussionmentioning
confidence: 90%
“…In general, this study identified a potential target for the development of novel antiviral therapeutic strategies. On the other hand, based on current research findings, many viral proteins participated in the regulation of autophagy, such as A137R, MGF-505-7R, K205R, L83L, E199L, A179L, and MGF-110-9L ( 38 , 40 43 , 53 , 54 ). Thus, we concluded that autophagy may play an important role in the regulation of ASFV replication, and the mechanism between viral protein and autophagy deserves further study.…”
Section: Discussionmentioning
confidence: 90%
“…Some of these viral proteins seem to affect the first steps of the pathway, such as the QP383R that interacts with cGAS, preventing DNA binding [13] or C129R and EP364R that degrade cGAMP [12]. Other ASFV proteins counteract TBK1 action by inducing its degradation, as A137R [18], MGF-110-9L [17], MGF360-11L or MGF505-7R do, the two latter further interacting with IRF7 [48,49]; while others degrade IRF3, such as M1249L or MGF360-14L [50,51] or inhibit its activation, such as E120R, E301R or S137R [52][53][54]. Multiple ASFV proteins seem to interact with STING, leading to counteract its activation, such as B175L, D117L (P17), MGF-505-7R, MGF505-11R, EP402R (CD2v) or L83L [14][15][16]19,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…We first hypothesized that the absence of this protein was linked to virulence in domestic pigs, similar to other ASFV proteins involved in the control of the cGAS/STING pathway, which have been found to be directly related to virulence. Examples of that would be ASFV MGF-505-7R [15], A137R [18,33], or MGF-110-9L [17,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation